Progress of Conjugated Polymers as Emerging Thermoelectric Materials. (June 2022) - Wang, Suhao; Zuo, Guangzheng; Kim, Jongho; Sirringhaus, Henning
Graphical abstract: Image, graphical abstract Abstract: Thanks to the combined efforts of scientists in several research fields, the preceding decade has witnessed considerable progress in the use of conjugated polymers as emerging thermoelectric materials leading to significant improvements in performance and demonstration of a number of diverse applications. Despite these recent advances, systematic assessments of the impact of molecular design on thermoelectric properties are scarce. Although several reviews marginally highlight the role of chemical structure, the understanding of structure-performance relationships is still fragmented. An in-depth understanding of the relationship between molecular structure and thermoelectric properties will enable the rational design of next-generation thermoelectric polymers. To this end, this review showcases the state-of-the-art thermoelectric polymers, discusses structure-performance relationships, suggests strategies for improving thermoelectric performance that go beyond molecular design, and highlights some of the most impressive applications of thermoelectric polymers.